Student-Centered Approaches to Curriculum and Course Design - Hasibuan, Kalayo; Frista, Athyah; Fiveronika, Fiveronika (Universitas Pahlawan Tuanku Tambusai, 2025)
This literature review explores the principles and practices of student-centered approaches to curriculum and course design, focusing on how these pedagogical models prioritize the learner’s needs, interests, and active participation in the learning process. By synthesizing key research and theoretical perspectives, the review examines how student-centered approaches differ from traditional, teacher-driven instructional methods and highlights their impact on fostering critical thinking, creativity, and learner autonomy. Key strategies discussed include project-based learning, problem-based learning, and technology-aided learning, all of which emphasize hands-on, participatory approaches that engage students as active co-creators of their educational experiences. The review also considers how technology and digital tools can enhance student-centered learning environments by providing opportunities for personalized learning pathways, self-directed learning, and global collaboration. Through this synthesis, the review demonstrates the transformative potential of student-centered design in promoting deeper, more meaningful learning outcomes while preparing students for lifelong learning and problem-solving in an ever-evolving world.